Just on the Right Side of Wrong: (De)Legitimizing Feminism in Video Game Live Streaming. (July 2022) - Cullen, Amanda L. L.
The participation of women in video games continues to be interrogated, especially the participation of women who are, or are perceived to be, feminists. A considerable portion of the discourse on the appropriateness of feminism in live streaming takes place on Twitch and gaming subreddits. This paper applies a qualitative analysis to several Reddit threads that address the subject of feminism in live streaming. The analysis of subreddit comments about feminism in streaming suggest that many Twitch users believe feminism is an ideology that is incompatible with video games and live streaming. Furthermore, many of these users believe that feminists actively harm live streaming communities. This paper presents an understanding of how and why the presence and legitimacy of feminism in games continues to be contested and demonstrates what is at stake for feminists who desire to participate in building a future for themselves in video game live streaming.